2020
DOI: 10.1002/app.50082
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic enhancement of mechanical, viscoelastic, transport, thermal, and radiation aging characteristics through chemically bonded interface in nanosilica reinforced EPDM‐CIIR blends

Abstract: The study investigates the influence of bis(3‐triethoxysilylpropyl)tetrasulfide (TESPT) grafted nanosilica (NS) reinforcement on the mechanical, viscoelastic, thermal, and transport characteristics as well as behavior after exposure to different cumulative γ‐radiation doses of EPDM‐CIIR blends for application in nuclear and hydrocarbon environments. The tensile strength and modulus of the nanocomposites were enhanced upto 64% and 118%, respectively whereas solvent diffusion coefficient reduced by 22%. The degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…It was clearly shown that a decrease in swelling ratio by irradiation, results in increase in crosslinking density and hence decrease in the elongation 34 . Gamma radiation induced free radicals or unpaired electrons have played key role in the fromation of crosslinks 35,39 . The strain deformation capability of EPDM composites is reduced and attributed to crosslinking which limits the ultimate chain stretch 40 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was clearly shown that a decrease in swelling ratio by irradiation, results in increase in crosslinking density and hence decrease in the elongation 34 . Gamma radiation induced free radicals or unpaired electrons have played key role in the fromation of crosslinks 35,39 . The strain deformation capability of EPDM composites is reduced and attributed to crosslinking which limits the ultimate chain stretch 40 .…”
Section: Resultsmentioning
confidence: 99%
“…34 Gamma radiation induced free radicals or unpaired electrons have played key role in the fromation of crosslinks. 35,39 The strain deformation capability of EPDM composites is reduced and attributed to crosslinking which limits the ultimate chain stretch. 40 There is possibility that an increase in the crosslink density give rise to saturation level of ultimate chain stretch for the EPDM composites.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…It should be noted that the phenomenon K f >> K r occurred in most research work about rubber-solvent systems [15][16][17]. In particular, in the study of cyclohexane in nanosilica-reinforced ethylene propylene diene monomer/isobutylene isoprene rubber, Neelesh Ashok found that the K f values were much lower than the K r values, and the n values were always higher than 1.0 [18]. However, all the above work for rubber-solvent systems did not elaborate on or limit the transport time or degree of solvent used for mathematical fitting, which were different from the 60% degree of drug release [19].…”
Section: Introductionmentioning
confidence: 99%
“…Neelesh Ashok et al [18] investigated the mechanical, viscoelastic, thermal, and transport properties of EPDM-CIIR blends reinforced with bis(3-triethoxysilylpropyl)tetrasulfide (TESPT)-grafted nano-silica after exposure to different cumulative radiation doses. The nanocomposites had a degradation onset temperature of 503 • C, compared to 485 • C for unfilled blends.…”
Section: Introductionmentioning
confidence: 99%